The Impact Of Subak Rice Field Conversion On Socio-Economic Welfare And Environmental Sustainability In North Kuta District, Badung Regency - I Gusti Ayu Eka Suwintari; Putu Wibby Prasetya (Politeknik Internasional Bali, 2025)
Badung Regency, as the main tourism center in Bali, has experienced massive agricultural land conversion to meet the needs of tourism facilities. The area of rice fields decreased from 9,072 hectares in 2019 to around 8,024 hectares in 2022, with an average conversion rate of around 95 hectares per year. This phenomenon has had a significant impact on the welfare of local communities who have lost their livelihoods in the agricultural sector, even though they have gained short-term economic benefits from the sale of land. This study aims to analyze land conversion patterns and evaluate their impact on the economic, social, and cultural welfare of local communities. The research method uses a mixed approach, including literature studies, quantitative surveys of affected communities, stakeholder interviews, and satellite image-based spatial analysis. This study is expected to provide a comprehensive understanding so that land management can balance the needs of tourism development and the preservation of community and environmental welfare.